The Impact of "Teman Bunda" Pocket Book Print Media Education on Mothers' Knowledge of Toddler Growth and Development - Nurun Nikmah; Rila Rindi Antina; Selvia Nurul Qomari; Dita Puspita Sari (PROFESSIONAL HEALTH JOURNAL, 2025)
Good nutritional status is crucial to support a child's growth and development. The high prevalence of nutritional and developmental issues in toddlers is, in part, influenced by the mother's knowledge. This study aims to assess the impact of providing education using the "Teman Bunda" Pocket Book as a print media tool. This research utilized a quasi-experimental method with a pretest-posttest design. The study sample included 88 respondents. The results showed that, prior to the educational intervention using the "Teman Bunda" Pocket Book, 14 respondents (16%) had poor knowledge, 32 respondents (36%) had adequate knowledge, and 42 respondents (48%) had good knowledge. After the intervention, 8 respondents (9%) still had poor knowledge, 24 respondents (27%) had adequate knowledge, and 56 respondents (64%) had good knowledge. Statistical analysis using the Marginal Homogeneity Test yielded a p-value of 0.001 < α 0.05 (p = 0.001), indicating that H0 is rejected. This confirms that the educational intervention using the "Teman Bunda" Pocket Book Print Media significantly influences mothers' knowledge regarding toddler growth and development. In conclusion, this study demonstrates that the "Teman Bunda" Pocket Book Print Media has a significant positive effect on improving mothers' knowledge about toddler growth and development.